Economic Concentration and Price Inflexibility - Backman, Jules (The Review of Economics and Statistics, 1958)
Although Means had compiled concentration and data for 94 industries, he based his conclusions on the chart covering 37 industries reproduced by Blair (page 427). Actually, in the original study,3 price data in relation to Census classification were considered adequate or fair for 7I industries serving national markets and for I3 industries serving other types of markets; data were poor for only 9 industries.4 In his presentation, Dr. Blair omitted Rufus Tucker's classic commentary upon Means's chart: 5